To correctly demonstrate polynomial addition, we need to add the like terms from the two polynomial expressions.
Let's look at the expression \((2x^2 + 6x + 1) + (3x^2 + 3x + 9)\):
- Combine the \(x^2\) terms: \(2x^2 + 3x^2 = 5x^2\)
- Combine the \(x\) terms: \(6x + 3x = 9x\)
- Combine the constant terms: \(1 + 9 = 10\)
Putting these together, we get: \[ (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \]
Now, let's analyze the options given:
- First Response: \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 13x^2 + 9x + 10 \) - Incorrect (the \(x^2\) terms were added incorrectly)
- Second Response: \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^4 + 9x^2 + 10 \) - Incorrect (the polynomial degree is wrong)
- Third Response: \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = -x^2 + 3x - 8 \) - Incorrect (completely wrong values)
- Fourth Response: \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \) - Correct
Therefore, the correct example demonstrating polynomial addition is the fourth response:
\((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10\).